Factor x2 - x - 90 = 0.

x2 - x - 90 = 0 in factored form is (x-10)(x+9)=0

Expert answered|andrewpallarca|Points 22272|

Question

Asked 6/4/2013 4:17:19 PM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

s

Rating

There are no new answers.

Factor the trinomial: x2 + 3x - 40 **Weegy:** (3x-2) squared is 9x^2 - 12x + 4. **User:** If f(x) = 2x and g(x) = 5x, calculate f(g(x)). **Weegy:** D. 5x - 4 is the answer. **User:** Express The square root of negative 12. in i notation. **User:** Solve by completing the square: x2 + 8x = -3. **User:** Simplify y-4 y 2 -16 **User:** Evaluate 64 to the one third power. **User:** Simplify 8-2 by making the exponent positive. **Weegy:** 8^-2 = 1/(8^2) = 1/64 **User:** Simplify y-2 by making the exponent positive **User:** Evaluate 125 to the one third power **User:** Simplify x-5 by making the exponent positive. (More)

Question

Updated 6/22/2014 4:44:42 AM

5 Answers/Comments

x^2 + 3x - 40 = (x - 5)(x + 8)

Added 6/22/2014 4:40:48 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/23/2014 1:18:46 PM]

f(x) = 2x and g(x) = 5x,

f(g(x)) = f(5x) = 2(5x) = 10x

f(g(x)) = f(5x) = 2(5x) = 10x

Added 6/22/2014 4:41:35 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/23/2014 1:19:05 PM]

x^2 + 8x = -3

x^2 + 8x + 16 = -3 + 16

(x + 4)^2 = 13

x + 4 = ± sqrt 13

x = -4 ± sqrt 13

x^2 + 8x + 16 = -3 + 16

(x + 4)^2 = 13

x + 4 = ± sqrt 13

x = -4 ± sqrt 13

Added 6/22/2014 4:43:42 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/23/2014 1:19:34 PM]

64 to the one third power is 4.

Added 6/22/2014 4:44:42 AM

This answer has been confirmed as correct and helpful.

Solve the quadratic equation x2 + 16x = -64 by factoring. **Weegy:** The answer for x2 + 16x = -64 is x = -8. **User:** Solve the quadratic equation 5x2 - 125 = 0. **Weegy:** The answer is (x+8) (x+8). (More)

Question

Expert Answered

Updated 8/19/2014 1:19:05 AM

1 Answer/Comment

5x^2 - 125 = 0

5(x^2 - 25) = 0

5(x + 5)(x - 5) = 0

x = -5 or x = 5

5(x^2 - 25) = 0

5(x + 5)(x - 5) = 0

x = -5 or x = 5

Added 8/19/2014 1:19:05 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [8/19/2014 1:22:27 AM]

32,766,199

questions answered

There are no comments.